Putting the Community into Organizational Science: Exploring the Construction of Knowledge Claims - Deetz, Stanley (Organization Science, 2000)
Like Weiss, I too dislike some of the postmodern writings on organizations. I too worry that shallow works given even more shallow and opportunistic readings can have negative social consequences. But I also recognize that most of Weiss's concerns are not unique to postmodern writings. Many of the problems he discusses could also be descriptive of work from different conceptual and methodological stances. Statistics are often contrived and misleading. Ethnography has at times aided colonization. Both social and physical sciences have at times produced bad theories and been put to very negative uses. Some early postmodernist theorists, Christians, and scientists, were Nazis, and elements of each of their fundamental conceptions could be co-opted to support this particular form of barbarism. This potential utilization, however, does not lead for me to a blanket condemnation of postmodernism, science, ethnography, religion, or statistics. Devotees of each have used their special understandings to fight tyranny. Both postmodernism and science also draw on fundamental conceptions that are productive, enable open choices, and help us see through the masters and ideologies of a particular time and place. I am less interested in blame than in finding what each can contribute. I look to an ongoing community discussion that helps us to do the best we can to sort out the good from the bad, and I hope that the current set of essays helps stimulate a positive dialogue.